Nivel de Incumplimiento de las Normas Para La Promoción Publicitaria en Oficinas Farmacéuticas, Región La Libertad – 2015 - Zavaleta Rodriguez, Marianelly Estefany (2018)
The objective of this research was: to determine the level of noncompliance of the rules for the advertising promotion in drugstores of La Libertad region between the months of January and December, 2015. The sample consisted of 121 drugstores of La Libertad region, which were previously inspected. The study design was descriptive, retrospective and transversal. The technique used was the structured observation of the 249 advertising promotions files, with the verification of non-compliance of the rules for advertising promotions based on Law No. 29459, Law of Pharmaceutical Products, Medical Devices and Health Products, Chapter X , DS N ° 014-2011-SA, Regulation of Pharmaceutical Establishments, and its amendment DS Nº 002-2012-SA and DS N ° 016-2011-SA, Regulation for the Registry Control and sanitary surveillance of pharmaceutical products, medical devices and health products, and its amendment DS Nº 001-2012-SA, Chapter V. The results show a low level of non-compliance of the rules for advertising promotion (13.04%).Laboratories Teva Peru (17.39%), Arion Mason (13.04%) and Portugal (13.04%) were the main levels of non-compliance and Bismutol products (4.35%), Nastiflu (4.35%) ) and Multifort (4.35%) were the drugs with the highest number of observations